Thematic Contents of Preschool-Aged Children’s Utterances as Media to Shape Their Understanding of the World - Titik Sudartinah (UIN Salatiga, 2022)
Language ability develops greatly during preschool age. Triggered by the high curiosity that goes hand in hand with the exposures to others around them, preschool-aged children show great efforts to create a collection of vocabulary to help them learn and use language in real contexts. This research aims to identify the thematic contents of preschool-aged children’s utterances and explain the categories of these thematic contents to shape their understanding of the surrounding world. To answer these objectives, both qualitative and quantitative data were used. The qualitative data were the utterances of preschool-aged children when participating in conversations, while the quantitative data were the frequency of occurrence of each thematic content, which is used to support the qualitative interpretation. The data were collected during classroom sessions in two preschools in Yogyakarta, Indonesia for a one-week period. The participants were 29 preschool-aged children, whose age ranges from 3 to 5 years old. Audiovisual recordings, field notes, datasheets, and ELAN 5.5. and FLEx 8 software were the instruments for data collection and analysis. The results show that there are two main thematic contents expressed by these preschool-aged children, i.e., objects and people. These thematic contents can be detailed into 9 categories of objects and 4 categories of people. These support the overall interpretation revealing the picture of the world as perceived by the children. In general, through the thematic contents of their utterances, preschool-aged children try to build a complete understanding of the world they live in and these thematic contents also serve as the media for understanding the stance of their peers and teachers in a conversation.Keywords: preschool-aged children; thematic contents; utterances